ISOLASI JAMUR PEMBENTUK GUBAL PADA TANAMAN GAHARU (GYRINOPS VERSTEGII) (ISOLATION OF GUBAL FORMING FUNGI ON GAHARU (GYRINOPS VERSTEGII)) - MEGA, I MADE; AGUNG PHABIOLA, TRISNA (AGRITROP, 2010)
The study is aimed to explore the microbial isolates of agarwood (gubal gaharu)-forming plant aloes on ketimunan plant (Gyrinops verstegii). The study was coducted from June to October 2008 in the Laboratory of Soil Biology, Faculty of Agriculture, University of Udayana. The method used in this study were: the isolation of microbes with PDA medium, inoculation of isolate into ketimunan plants, evaluating the success of inoculation (injection). Parameters measured were: the color of mold, the color of agarwood/kemedangan, long agarwood, and the level of the smell of agarwood/kemedangan. The results showed that there were 14 species of fungi that able to form agarwood aloes on the plant ketimunan. All of these fungus were able to cause agarwood/kemedangan fragrant aloes, but the level of fragrance varies from slightly fragrant, fragrant, until very fragrant.